NMDA and AMPA receptors: development and status epilepticus - Szczurowska, E; Mareš, P (Physiological research, 2013)
Glutamate is the main excitatory neurotransmitter in the brain and ionotropic glutamate receptors mediate the majority of excitatory neurotransmission (Dingeldine et al. 1999). The high level of glutamatergic excitation allows the neonatal brain (the 2(nd) postnatal week in rat) to develop quickly but it also makes it highly prone to age-specific seizures that can cause lifelong neurological and cognitive disability (Haut et al. 2004). There are three types of ionotropic glutamate receptors (ligand-gated ion channels) named according to their prototypic agonists: N-methyl-D-aspartate (NMDA), 2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl) propanoic acid (AMPA) and kainate (KA). During early stages of postnatal development glutamate receptors of NMDA and AMPA type undergo intensive functional changes owing to modifications in their subunit composition (Carter et al. 1988, Watanabe et al. 1992, Monyer et al. 1994, Wenzel et al. 1997, Sun et al. 1998, Lilliu et al. 2001, Kumar et al. 2002, Matsuda et al. 2002, Wee et al. 2008, Henson et al. 2010, Pachernegg et al. 2012, Paoletti et al. 2013). Participation and role of these receptors in mechanisms of seizures and epilepsy became one of the main targets of intensive investigation (De Sarro et al. 2005, Di Maio et al. 2012, Rektor 2013). LiCl/Pilocarpine (LiCl/Pilo) induced status epilepticus is a model of severe seizures resulting in development temporal lobe epilepsy (TLE). This review will consider developmental changes and contribution of NMDA and AMPA receptors in LiCl/Pilo model of status epilepticus in immature rats.
Keywords: Synaptic Transmission; Animals, Newborn; Aging; Brain; AMPA receptory; Receptors, AMPA; neurony; novorozená zvířata; nervový přenos; status epilepticus; krysa rodu Rattus; Animals; Status Epilepticus; zvířata; Neurons; Rats; stárnutí; mozek; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu